Implementasi Kebijakan Kurikulum Kebaharian di SMA Hang Tuah 5 Sidoarjo - Sugiarto Sugiarto; A Subianto; Nuhman Nuhman (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The Sidoarjo regional government in exploiting the potential of its area, has made various efforts to improve the level of community welfare. One of the significant potential of the Sidoarjo area is in the marine sector. The existence of these marine products, must be balanced with the preparation of human resources in the field of maritime affairs, one of which is through education with the issuance of Sidoarjo Regent's Regulation No. 16 of 2012 concerning the implementation of local content curriculum. This policy is expected to be able to cover the field of maritime in accordance with the potential of the Sidoarjo region and be implemented in high school level educational institutions. The purpose of this study was to determine the application of the Sidoarjo Regent's policy on the curriculum of local maritime and to analyze the factors that hamper and support it. This research is a qualitative research, with data collection techniques through observation, interviews and documentation. While data analysis techniques include data reduction, data presentation and conclusions. The results of this study indicate that the curriculum policies on local maritime have not yet been fully implemented in high school level educational institutions. However, efforts that have been made by schools to meet the minimum capability according to the Sidoarjo Regent's regulations can be achieved. This research is expected to be able to contribute to educational institutions in the form of the formulation of policies to improve the education of educators at higher levels in the field of maritime affairs, recruitment of education personnel from graduates of maritime graduates or the like and standardization of marine education facilities.